1978
DOI: 10.1136/jcp.31.4.361
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol formed from arabinose: a rapid method for detecting Escherichia coli.

Abstract: Head-space gas-liquid chromatography showed that Escherichia col are consistent in their ability to ferment arabinose with the production of ethanol. In both still and shaken cultures ethanol production is closely aligned with growth. Also ethanol production is related to inoculum size so that varying sizes of inocula may be distinguished by choosing a time of sampling early in growth. The method is suitable as a rapid test for E. coli and is applicable for use in detecting E. coli urinary tract infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1978
1978
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…One drawback is the inability to tell apart Klebsiella aerogenes from E. coli, since both species ferment lactose to ethanol. In a similar study, 49 strains of E. coli were grown in media supplemented with arabinose [80]. It was confirmed that the bacteria produce ethanol with a maximum concentration achieved after eight hours.…”
Section: Detection Of Urinary Tract Infection Using Volatile Organic mentioning
confidence: 71%
“…One drawback is the inability to tell apart Klebsiella aerogenes from E. coli, since both species ferment lactose to ethanol. In a similar study, 49 strains of E. coli were grown in media supplemented with arabinose [80]. It was confirmed that the bacteria produce ethanol with a maximum concentration achieved after eight hours.…”
Section: Detection Of Urinary Tract Infection Using Volatile Organic mentioning
confidence: 71%
“…The suspension was transferred to a 28-ml screw-capped bottle and incubated with shaking at 370C for four hours. The resulting culture was examined for ethanol and dimethyl disulphide by means of head-space gasliquid chromatography as described by Coloe (1978).…”
Section: Methodsmentioning
confidence: 99%
“…More recent culture methods such as the use of dip-slides (Craig and Kunin, 1972) do show the number of organisms present, but they are only marginally faster than routine culture methods and cannot be called rapid. This paper describes a rapid way of quantifying Escherichia coli and Proteus mirabilis in urine by a method based on those of Coloe (1978) and Hayward et al (1977).…”
mentioning
confidence: 99%